Numerical investigation of stagnation point flow over a stretching sheet with convective boundary conditions recent trends on boundary value problems and related topics - Muhammad Khairul Anuar, Mohamed; Mohd Zuki, Salleh; Roslinda, Nazar; Anuar, Ishak (Springer International Publishing AG, 2013)
In this study, the mathematical modeling for stagnation point flow over a stretching surface with convective boundary conditions is considered. The transformed boundary layer equations are solved numerically using the shooting method. Numerical solutions are obtained for the skin friction coefficient, the surface temperature as well as the velocity profiles. The features of the flow and heat transfer characteristics for various values of the Prandtl number, stretching parameter and conjugate parameter are analyzed and discussed.